Ментовская работа: [повести] / Данил Корецкий ; [художник В. Ю. Щербаков] - Корецкий Данил Аркадьевич (Черная кошка, 1997)
Экземпляры: ф.21 (2004) / Инвентарный номер: 47687 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: К 66 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44